Ecological Pressures In Pusong Harbour: Integrated Assessment Of Water Quality, Nutrient Enrichment, And Pollution Index - Cut Meurah Nurul 'Akla; Malik Pajar Lubis; Erniati Erniati; Rian Firdaus; Imamshadiqin Imamshadiqin; Imanullah Imanullah (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2025)
ABSTRACTPusong Harbor in Lhokseumawe City doubles as a center for fisheries activities as well as a habitat for marine biota, making it vulnerable to pollution pressure from anthropogenic activities. This study aims to assess water quality through the analysis of physico-chemical parameters, nutrient content (nitrate and phosphate), pollution index, and spatial variation patterns using a multivariate approach. Measurements were taken at three stations representing the locations of boat moorings, settlements, and fish farms. The measurement results showed that basic parameters such as salinity (32-33‰), pH (7.5-8.0), dissolved oxygen (5.8-6.3 mg/L), and BOD (1.6-3.6 mg/L) were still within the quality standard range, but the brightness level was low (0.8-0.9 m) and the phosphate concentration was very high (7.2-10.1 mg/L), exceeding the quality standard by hundreds of times. The pollution index based on the harbor quality standard showed a Slightly polluted (PI = 1.09-1.11), but based on the marine biota quality standard it was classified as